Find n → ∞ lim r = 1 ∑ n arctan ( 2 r 2 1 ) in degrees.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
lim n → ∞ ∑ r = 1 n arctan ( 2 r 2 1 ) = lim n → ∞ ∑ r = 1 n arctan ( 4 r 2 2 ) = lim n → ∞ ∑ r = 1 n arctan ( 1 + ( 2 r + 1 ) ( 2 r − 1 ) ( 2 r + 1 ) − ( 2 r − 1 ) ) = lim n → ∞ ∑ r = 1 n arctan ( 2 r + 1 ) − arctan ( 2 r − 1 ) = lim n → ∞ arctan ( 2 n + 1 ) − arctan 1 = 9 0 − 4 5 = 4 5
Problem Loading...
Note Loading...
Set Loading...
Let θ n = r = 1 ∑ n arctan ( 2 r 2 1 ) . Then we have:
θ 1 θ 2 θ 3 = arctan ( 2 1 ) = arctan ( 2 1 ) + arctan ( 8 1 ) = arctan ( 1 − 2 1 ⋅ 8 1 2 1 + 8 1 ) = arctan ( 3 2 ) = arctan ( 3 2 ) + arctan ( 1 8 1 ) = arctan ( 1 − 3 2 ⋅ 1 8 1 3 2 + 1 8 1 ) = arctan ( 4 3 )
It appears that θ n = arctan ( n + 1 n ) and we can prove it by induction that the claim is true for all n ≥ 1 . We know that the claim is true for n = 1 . Assume that it is true for n , then:
θ n + 1 = θ n + arctan ( 2 ( n + 1 ) 2 1 ) = arctan ( n + 1 n ) + arctan ( 2 ( n + 1 ) 2 1 ) = arctan ( 1 − n + 1 n ⋅ 2 ( n + 1 ) 2 1 n + 1 n + 2 ( n + 1 ) 2 1 ) = arctan ( 2 ( n + 1 ) 3 − n ( n + 1 ) ( 2 n 2 + 2 n + 1 ) ) = arctan ( 2 ( n 3 + 3 n 2 + 3 n + 1 ) − n ( n + 1 ) ( 2 n 2 + 2 n + 1 ) ) = arctan ( 2 n 3 + 6 n 2 + 5 n + 2 ( n + 1 ) ( 2 n 2 + 2 n + 1 ) ) = arctan ( ( n + 2 ) ( 2 n 2 + 2 n + 1 ) ( n + 1 ) ( 2 n 2 + 2 n + 1 ) ) = arctan ( n + 2 n + 1 )
Therefore, the claim is also true for n + 1 and hence true for all n ≥ 1 .
Then we have n → ∞ lim r = 1 ∑ n arctan ( 2 r 2 1 ) = n → ∞ lim arctan ( n + 1 n ) = arctan ( 1 ) = 4 π = 4 5 ∘ .